MANAGEMENT OF ENTREPRENEURIAL RISKS FROM THE PERSPECTIVE OF ECONOMIC SECURITY OF A BUSINESS - NIANKO, Vitalii; YOLKIN, Andriy; YABLONSKII, Taras; BABYAK, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Perception of risk and decision-making under conditions of uncertainty are defining characteristics of entrepreneurship. For Ukrainian businesses, the conditions have always been characterized by a high level of risk, and the full-scale war has significantly increased the number of threats. The article addresses the current issues of managing entrepreneurial risks, particularly in the context of increased uncertainty caused by the war. It analyzes the essence of the concepts of "risk" and "entrepreneurial risk" with consideration of their evolutionary development. It is determined that risk is an inherent part of entrepreneurial activity, combining threats and opportunities, stimulating innovative solutions and adaptation to change. An analysis of scientific works by leading researchers highlights key approaches to defining the essence of risk, including: probabilistic, economic, dualistic, and complex. These approaches emphasize the multifaceted nature of the concept, covering uncertainty, potential losses, as well as the conscious acceptance of risky decisions. Special attention is given to the characteristics of modern approaches to risk management, which encompass identification, assessment, monitoring, and minimization of the impact of negative factors. The article is based on the results of an analysis of the works of leading scholars in the field of risk management and the experience of implementing anti-crisis measures in enterprises. Entrepreneurial risk is considered an inseparable element of economic activity that requires effective management. It is noted that effective management of entrepreneurial risks is a key factor for ensuring competitiveness and sustainable development in the long term.